PREVALENCE OF DIFFERENT TYPES OF THYROID DISORDERS IN A GROUP OF CHILDREN WITH DIABETES MELLITUS TYPE 1 - Adriana, Gherbon (European Scientific Journal, ESJ, 2013)
Background&Aims: Thyroid disorders are frequently associated with diabetes in clinical practice. In type 1 diabetes, because autoimmune etiology it is often associated with autoimmune thyroid disease (chronic autoimmune thyroiditis, Basedow-Graves disease). The purpose of this study is to asses the prevalence of different types of thyroid disorders in a group of children with diabetes mellitus (DM) type 1. Methods: The studied group was represented by 83 children with diabetes mellitus type 1 (71 F and 12 M), aged between 7 and 17 years. Were used clinical, biochemical and imaging parameters. Results: Regarding the type of thyroid disease, prevailed ACT - 65.06% (87.03% F vs. 12.97% M, p<0.001, X2= 59.26), followed by diffuse euthyroid goiter - 30.12% (80% F vs. 20% M, p<0.001, X2= 18) and Graves-Basedow disease - 4.82% (100% F vs. 0% M, p = 0.006, X2= 8). For each thyroid disease we determined the actual mean age, the onset mean age of thyroid disease and diabetes, the mean duration of diabetes and thyroid disease, mean BMI, glucose and HbA1c. We found significant differences between these three thyroid disease regarding actual age, onset age of diabetes, diabetes and thyroid disease duration. We don’t found significant differences regarding BMI, blood glucose and HbA1c. Conclusion: In children with type 1 diabetes we found a net predominance of female and were prevailed autoimmune diseases such as part of the polyglandular autoimmune syndrome.